Audit Report Lag: Institutional Ownership, Gender Diversity, and Audit Tenure - Nurbaiti, Annisa; Qadli, Faruq (UNIVERSITAS PAKUAN, 2022)
This study aims to reveal simultaneously and partially the influence of institutional ownership, gender diversity, and audit tenure on audit report lag. The research method used is quantitative. The population in this study is companies registered in Consumer Non-Cyclicals Sector Companies Listed on The Indonesian Stock Exchange in 2017-2021. And using a purposive sampling technique with a total sample of 290, representing 58 companies over five years. Panel data regression analysis was carried out in this study using Eviews 12 software. The study results show that institutional ownership, gender diversity, and audit tenure simultaneously affect audit report lag. Partially, institutional ownership has a significant negative effect on audit report lag, while gender diversity and audit tenure have no effect. A high level of institutional ownership influences audit report lag in this study. In contrast, the presence of women on audit committees and the number of auditor tenures do not affect the duration of audit report lag.